Duration of periconceptional folic acid supplementation in women booking for antenatal care. Issue 2 (5th October 2016) - Cawley, Shona; Mullaney, Laura; Kennedy, Rachel; Farren, Maria; McCartney, Daniel; Turner, Michael J
Abstract: Objective: To provide accurate estimates of the commencement time, duration and dosage of folic acid (FA) supplementation taken by Irish women in the periconceptional period. The study also aimed to establish the factors associated with optimal FA supplementation practices. Design: Cross-sectional observational study. Women's clinical and sociodemographic details were computerised. Maternal weight and height were measured before calculating BMI. Detailed FA supplementation questionnaires were completed under the supervision of a trained researcher. Setting: A large university maternity hospital, Republic of Ireland, January 2014–April 2016. Subjects: Women ( n 856) recruited at their convenience in the first trimester. Results: While almost all of the women (97 %) were taking FA at enrolment, only one in four women took FA for at least 12 weeks preconceptionally ( n 208). Among the 44 % of women who were supplementing with FA preconceptionally, 44 % (162/370) reported taking FA for less than the 12 weeks required to achieve optimal red-blood-cell folate levels for prevention of neural tube defects. On multivariate analysis, only planned pregnancy and nulliparity were associated with taking FA for at least 12 weeks preconceptionally. Among women who only took FA postconceptionally, almost two-thirds commenced it after day 28 of their pregnancy when the neural tube had already closed. Conclusions: As the timing of FA was suboptimal both before and after conception, we recommend that current national FA guidelines need to be reviewed.